A Study on Interactive–Based Learning Media to Strengthen the Profile of Pancasila Student in Elementary School (JED (Jurnal Etika Demokrasi), 2021)
This study aimed to determine the interactive-based learning media to strengthen the profile of Pancasila students in elementary schools. This type of research was literature study. The results showed that interactive-based learning media to strengthen the profile of Pancasila students in elementary schools can increase motivation in learning by the emergence of independent characters as a part of the character in the profile of Pancasila students in elementary schools. It was also seen as a facility in active learning for students to strengthen the profile of Pancasila students in elementary schools as well as to lead to a tendency to have a good character component. In addition, this learning media eased students to understand learning in term of strengthening the profile of Pancasila students in elementary schools by the emergence of the character of critical and creative reasoning. The use of the interactive –based learning media could build conducive and enjoyable learning atmosphere. Penelitian ini bertujuan untuk mengetahui  media pembelajaran berbasis interaktif untuk memperkuat profil pelajar pancasila di Sekolah Dasar. Jenis penelitian ini ialah kualitatif studi literatur. Hasil penelitian menunjukan jika media pembelajaran berbasis interaktif untuk memperkuat profil pelajar pancasila di Sekolah Dasar dapat 1) Meningkatkan motivasi dalam pembelajaran dengan munculnya karakter mandiri sebagai bagian karakter dalam profil pelajar pancasila di Sekolah Dasar. 2) Menjadi fasilitas dalam belajar aktif bagi siswa untuk memperkuat profil pelajar pancasila di Sekolah Dasar ialah mengarah pada  kecendrungan kepemilikan komponen karakter yang baik. 3) Memudahkan siswa dalam memahami pembelajaran  untuk memperkuat profil pelajar pancasila di Sekolah Dasar ialah dengan munculnya karakter nalar kritis dan kreatif. Penggunaan media pembelajaran berbasis interaktif dapat membangun suasana pembelajaran yang kondusif dan menyenangkan.